The Role of Foreign Investments in Ensuring the Financial Stability of The Economy - Primova Shakhlo; Khayitov Vazirbek; Khayitov Marvarbek Sherbekovich (European Science Publishing, 2024)
Since the first years of independence, Uzbekistan has determined its own direction of development of the national economy. As a result of his timely understanding of the incomparable role of investments in the development and stability of the economy, there was an increase in attention to investments, especially foreign investments, which led to the development of investment activities in our country. came It should be noted that today's development of investment activity is a product of the rational investment policy of our government.